Memorandum "Open Metadata". Open Access to Documentation Forms and Item Catalogs in Healthcare - Dugas, M.; Joeckel, K-H; Friede, T.; Gefeller, Olaf; Kieser, M.; Marschollek, M.; Ammenwerth, E.; Roehrig, R.; Knaup-Gregori, P.; Prokosch, Hans-Ulrich (Methods of Information in Medicine, 2015)
At present, most documentation forms and item catalogs in healthcare are not accessible to the public. This applies to assessment forms of routine patient care as well as case report forms (CRFs) of clinical and epidemiological studies. On behalf of the German chairs for Medical Informatics, Biometry and Epidemiology six recommendations to developers and users of documentation forms in healthcare were developed. Open access to medical documentation forms could substantially improve information systems in healthcare and medical research networks. Therefore these forms should be made available to the scientific community, their use should not be unduly restricted, they should be published in a sustainable way using international standards and sources of documentation forms should be referenced in scientific publications.
EVALuna2:147